Designing options to narrow gender gaps in agricultural value chains using a resilience lens: Evidence from the Tahoua region of Niger - Nordehn, Caitleen (Cultural Practice, 2019)
Presented by Caitleen Nordehn (Cultural Practice), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.